Development and Characterization of Solid Self-emulsifying Drug Delivery System Containing Nateglinide - Suvarna, Vasanti (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: To develop self-emulsifying drug delivery system (SEDDS) of nateglinide to convert it into solid SEDDS (S-SEDDS) aerosil-200 as adsorbent. Materials and Methods: Nateglinide solid self-micro emulsifying drug delivery system (S-SMEDDS) formulation was prepared by adsorption to solid carrier technique, where the liquid SMEDDS are allowed to adsorb onto the surface of free flowing aerosil-200. Solubility study, ternary phase diagram, robustness to dilution, viscosity determination, cloud point measurement, thermodynamic stability study, and globule size analysis were adopted to optimize liquid SEDDS. S-SEDDS were evaluated for various studies including in vivo study. The optimized liquid SEDDS formulation consisted of nateglinide, capyrol-90, tween 80, Transcutol P. Results: The results of this study suggest the potential use of developed S-SEDDS formulation for the delivery of poorly water-soluble drug nateglinide. Conclusion: The developed S-SMEDDS is a promising strategy for solubility enhancement of poorly water-soluble drug nateglinide.